Pain as metaphor: metaphor and medicine. Issue 1 (7th August 2015) - Neilson, Shane
Abstract : Like many other disciplines, medicine often resorts to metaphor in order to explain complicated concepts that are imperfectly understood. But what happens when medicine's metaphors close off thinking, restricting interpretations and opinions to those of the negative kind? This paper considers the deleterious effects of destructive metaphors that cluster around pain. First, the metaphoric basis of all knowledge is introduced. Next, a particular subset of medical metaphors in the domain of neurology (doors/keys/wires) are shown to encourage mechanistic thinking. Because schematics are often used in medical textbooks to simplify the complex, this paper traces the visual metaphors implied in such schematics. Mechanistic-metaphorical thinking results in the accumulation of vast amounts of data through experimentation, but this paper asks what the real value of the information is since patients can generally only expect modest benefits – or none at all – for relief from chronic pain conditions. Elucidation of mechanism through careful experimentation creates an illusion of vast medical knowledge that, to a significant degree, is metaphor-based. This paper argues that for pain outcomes to change, our metaphors must change first.